1989
DOI: 10.1002/1097-0142(19890301)63:5<976::aid-cncr2820630532>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in aging women. A population-based study of contrasts in stage, surgery, and survival

Abstract: Over 43% of the newly diagnosed breast cancers in the US occur in women 65 years or older. Yet little attention is devoted to the age-associated aspects of this malignancy. This study uses data on more than 125,000 women diagnosed from 1973 to 1984 to examine the influence of advancing age on breast cancer. The National Cancer Institute's Surveillance, Epidemiology, and End Results Program provides information on disease stage, surgery, histologic type, and survival time to compare and contrast women in all ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
103
2
3

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(115 citation statements)
references
References 9 publications
7
103
2
3
Order By: Relevance
“…Similar findings have been reported from various countries (Polednak, 1986;Yancik et al, 1989;Coates et al, 1992;Afzelius et al, 1994;Fowble et al, 1994;Ramirez et al, 1999). Several explanations why patient delay is more often found among older women have been suggested.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings have been reported from various countries (Polednak, 1986;Yancik et al, 1989;Coates et al, 1992;Afzelius et al, 1994;Fowble et al, 1994;Ramirez et al, 1999). Several explanations why patient delay is more often found among older women have been suggested.…”
Section: Discussionsupporting
confidence: 87%
“…Older women were more likely to present with locally advanced and metastatic disease, as has previously been shown (Yancik et al, 1989). This excess of advanced disease in the older age group persists even when symptomatic patients only were examined.…”
Section: Discussion Tumour Stagesupporting
confidence: 65%
“…This dilutes any survival benefit from breast cancer treatment so differences may be difficult to detect. Stage at presentation also differs in older women because they are less likely to self-examine (Siahpush and Singh, 2002) and therefore the size of the primary cancer is greater at diagnosis (Diab et al, 2000;Golledge et al, 2000), and the incidence of advanced disease may be greater (Yancik et al, 1989).…”
Section: Stage Differences At Presentationmentioning
confidence: 99%
“…6 -9 Multivariate analyses to assess associations of age and menopausal status with other clinical and pathologic characteristics have not consistently retained either variable as an independent adverse prognosticator, 8 although several multivariate analyses have indicated that young age or premenopausal status are independent predictors of disease recurrence. 10 -13 In addition, a few studies have found that those women at the extremes of age, i.e., premenopausal women younger than 33 years of age 11 or postmenopausal women older than 80 -85 years of age, 3,14 had a worse prognosis than other age groups.…”
mentioning
confidence: 99%